PENGARUH PENDEKATAN PEMBELAJARAN DAN KREATIVITAS TERHADAP PEMAHAMAN KONSEP IPA DI SEKOLAH DASAR - Zulafni Zulafni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This article aims to prove the influence of learning and creativity approaches to understanding the concept of Natural Sciences (IPA). Quasi-experimental research uses a pre-test post-test control group design. The study population was Al-Falah Islamic Elementary School, Jambi City with a sample of class VI students. Data analysis uses two-way variance analysis (ANAVA). The results showed the following findings: 1) the influence of students' understanding of the science concept learned by the process skills approach was different from the students taught by conventional approaches, 2) the influence of the understanding of science concepts of students who have high creativity learned by the process skills approach different from students who have high creativity taught by conventional approaches, 3) Understanding of science concepts students who have low creativity who are taught by the process skills approach are relatively the same as students who have low creativity taught by conventional approaches, 4) There is no significant interaction between the use of process skills approaches and conventional approaches to creativity towards understanding the science concept. Keywords: learning approach, creativity, understanding, science concept